Skin gluten-related disorders: new and old cutaneous manifestations to be considered - Verdelli, Alice; Corrà, Alberto; Mariotti, Elena Biancamaria; Aimo, Cristina; Quintarelli, Lavinia; Ruffo di Calabria, Valentina; Donati, Marta Elettra; Bonciolini, Veronica; Antiga, Emiliano; Caproni, Marzia (Frontiers in Medicine, 2023)
The term gluten-related disorders (GRD) refer to a spectrum of different clinical manifestations triggered by the ingestion of gluten in genetically susceptible individuals, including coeliac disease (CD), wheat allergy and non-celiac gluten sensitivity (NCGS). GRD are characterized by a large variety of clinical presentations with both intestinal and extra-intestinal manifestations. The latter may affect almost every organ of the body, including the skin. Besides the well-known association between CD and dermatitis herpetiformis, considered as the cutaneous specific manifestation of CD, many other muco-cutaneous disorders have been associated to GRD. In this review, we analyzed the main features of dermatological diseases with a proven association with GRD and those that improve after a gluten-free diet, focusing on the newly described cutaneous manifestations associated with NCGS. Our main hypothesis is that a “cutaneous-gluten sensitivity”, as specific cutaneous manifestation of NCGS, may exist and could represent a diagnostic marker of NCGS.